The relationship between tax avoidance and firm value with income smoothing: A comparison between classical and Bayesian econometric in multilevel models - Akbari, Farzana; Salehi, Mahdi; Bagherpour Vlashani, Mohammad Ali (International journal of organizational analysis (2005), 2019)
PurposeThe purpose of this paper is to investigate the relationship between tax avoidance, firm value and managerial ability in Tehran Stock Exchange and Over the Counter (OTC), according to the related theoretical foundations.Design/methodology/approachTo calculate the managerial ability in this study, DEA is used based on the accounting data, company profile and industry and the hypotheses are estimated in a period of 12 years during 2004 to 2015 in TSE and OTC. Within the previous studies, to test the hypotheses, only the classical regression method is usually used and most of the times the effect of macroeconomic variables is not considered. In this study, in a new act for testing the hypotheses, three statistical methods are used, that is, classical regression models, mixed effects multilevel models and Bayesian multilevel models. Also in this study, the test of structural change is used to control the effects of macroeconomic variables, like inflation and other economic and political influence, on the results.FindingsThe results of these three methods show that the effect of income smoothing and earnings quality on the relationship between tax avoidance and firm value are significant.Originality/valueAlthough several studies are conducted so far on the subject of the study, the current study is the first project which combined Bayesian econometrics. Therefore, the results are quite noble.